AFTER SECURITISATION: DIPLOMATS AS DE-SECURITISERS - Neumann, Iver B. (Baltic Journal of Political Science, 2012)
After securitisation, there comes the further intensivation of a conflict, or violisation, or de-securitization. De-securitisation has many forms, one being diplomatisation. The article discusses peace and reconciliation work by states that are third parties to a conflict, and fastens on the pioneering state in terms of institutionalization, which is Norway. Following the Cold War, the Norwegian Ministry of Foreign Affairs engaged in this field broadly. Institutionalisation hit during the 2000s. Norwegian diplomacy facilitators think of de-securitisation in four steps: mapping the parties to a conflict, clearing their path to the table, assisting in their deliberations going across that table, being indirectly involved in the monitoring of agreements. The article concludes with a suggestion to the Copenhagen School. By adapting Austin and Searle’s speech act perspective, Wittgenstein’s general understanding of linguistic and other practices have been left behind. It is time to leave the cold analytics of speech act theory behind and reclaim the full thrust of Wittgenstein’s work, which was geared towards the constitutive role of practices for everything social. We need more empirical studies of violising practices, as well as of de-securitising legal and diplomatic practices.